2002
DOI: 10.1038/sj.onc.1205238
|View full text |Cite
|
Sign up to set email alerts
|

The subcellular localization of cyclin dependent kinase 2 determines the fate of mesangial cells: role in apoptosis and proliferation

Abstract: Apoptosis is closely linked to proliferation. In this study we showed that inducing apoptosis in mouse mesangial cells with ultraviolet (UV) irradiation was associated with increased cyclin A-cyclin dependent kinase (CDK) 2 activity. Inhibiting CDK2 activity with Roscovitine or dominant negative mutant reduced apoptosis. Because apoptosis typically begins in the cytoplasm, we tested the hypothesis that the subcellular localization of CDK2 determines the proliferative or apoptotic fate of the cell. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 42 publications
6
45
1
Order By: Relevance
“…Recently, it has been shown that the nucleocytoplasmic translocation of Cdk2 is under the control of p42/p44 MAPKs in fibroblasts (43,44). Cytoplasmic mislocalization of Cdk2 has also been reported to be a key event in vitamin D-mediated growth inhibition of prostate cancer cells (45) and in irradiation-induced apoptosis in mouse mesangial cells (46). In this study, we show that the subcellular localization of Cdk2 provides a novel mechanism whereby p38 MAPKs could regulate cell cycle progression.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, it has been shown that the nucleocytoplasmic translocation of Cdk2 is under the control of p42/p44 MAPKs in fibroblasts (43,44). Cytoplasmic mislocalization of Cdk2 has also been reported to be a key event in vitamin D-mediated growth inhibition of prostate cancer cells (45) and in irradiation-induced apoptosis in mouse mesangial cells (46). In this study, we show that the subcellular localization of Cdk2 provides a novel mechanism whereby p38 MAPKs could regulate cell cycle progression.…”
Section: Discussionmentioning
confidence: 64%
“…The rapid upregulation of Cdk2 activity is functionally associated with the onset of apoptosis in several experimental systems, including growth factor-deprived human endothelial cells, irradiated lymphocytes, heat shocked cells, and dexamethasone-treated cells (Levkau et al, 1998;Hiromura et al, 2002;Choi et al, 2007). Thus, Cdk2, a key regulator of the cell cycle, has been suggested to play a role in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cdk1/cyclin B1 activity shields human cells against extrinsic death stimuli (Matthess et al, 2010). Cdk2 activation is mainly detected in apoptotic cells that exhibit G 1 /S phase arrest, as observed in ultraviolet irradiation-treated mesangial cells (Hiromura et al, 2002), etoposide-induced human leukemic cells (Choi et al, 2007;Bastin-Coyette et al, 2011), growth factor-deprived HUVEC cells (Levkau et al, 1998), G-Rh2-induced human hepatoma cells (Jin et al, 2000), panaxadiol-induced SK-HEP-1 cells (Jin et al, 2003). In previous reports, we showed that Cdk2 but not Cdc2 is selectively up-regulated and this upregulation is required for the induction of apoptosis in several cancer cell lines, including SK-HEP-1 cells and HeLa cells induced by treatment with ginsenoside-Rh2 (G-Rh2) (Jin et al, 2000) or panaxadiol (Jin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis was measured by Hoechst 33342 (Dojindo Molecular Technologies, Tokyo, Japan) staining and by careful morphological analysis, as previously reported (13). Apoptotic cells were counted in six randomly selected fields and expressed as a percentage in triplicate.…”
Section: Methodsmentioning
confidence: 99%